2015
DOI: 10.1088/0031-9155/60/22/8753
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing the Microsoft Kinect for Windows v2 for external head motion tracking for brain PET

Abstract: Medical imaging systems such as those used in positron emission tomography (PET) are capable of spatial resolutions that enable the imaging of small, functionally important brain structures. However, the quality of data from PET brain studies is often limited by subject motion during acquisition. This is particularly challenging for patients with neurological disorders or with dynamic research studies that can last 90 min or more. Restraining head movement during the scan does not eliminate motion entirely and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…The measured distance accuracy of the Kinect v2 sensors is similar to that reported by others for both v1 and v2 sensors: several millimeters which can be reduced to <2thinmathspacemm or better with an appropriate correction 13 , 14 , 18 , 20 . Where systems are to be used for a clinical application, particularly if that involves monitoring small movements of a patient, it is important to determine the magnitude and impact of any EMI effect.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The measured distance accuracy of the Kinect v2 sensors is similar to that reported by others for both v1 and v2 sensors: several millimeters which can be reduced to <2thinmathspacemm or better with an appropriate correction 13 , 14 , 18 , 20 . Where systems are to be used for a clinical application, particularly if that involves monitoring small movements of a patient, it is important to determine the magnitude and impact of any EMI effect.…”
Section: Discussionsupporting
confidence: 84%
“…Whilst these provide no information about the internal anatomy of the patient, they may be used in conjunction with ionizing radiation imaging to provide frequent or continuous monitoring throughout the radiation delivery, as they do not contribute to the radiation dose burden. Recently some groups have investigated surface monitoring for radiotherapy and PET imaging using consumer‐grade sensors designed for the entertainment industry — the Microsoft Kinect devices 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 . The potential advantage of commercial off‐the‐shelf (COTS) devices is the low cost (less than ~$1,400 for a Kinect device and accessories compared to upwards of $250,000 for the commercial medical systems), thus enabling many sensors in many rooms, depending on the application.…”
Section: Introductionmentioning
confidence: 99%
“…The Kinect v2 has already been used for external head motion tracking in brain PET scans,10 respiratory motion correction in PET scans11 and respiratory motion tracking in radiotherapy using a marker‐based system 12. Previous work has shown that the sensor has distance accuracy and precision of 1 to 2 mm after calibration, which is sufficient for breath‐hold monitoring where changes are 5 to 10 mm in magnitude 10, 11, 13, 14, 15.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that the sensor has distance accuracy and precision of 1 to 2 mm after calibration, which is sufficient for breath‐hold monitoring where changes are 5 to 10 mm in magnitude 10, 11, 13, 14, 15. In our previous work,13 we demonstrated that the Kinect v2 can be used safely in a radiation environment without image distortions caused by the radiation beam.…”
Section: Introductionmentioning
confidence: 99%
“…It has been made available as a royalty‐free development platform with a free software development kit (SDK) containing many sample applications . This open‐sourced availability has allowed Kinect developers to create an array of applications for the medical community; from touch‐less panning of CT scans during surgery to respiratory motion tracking for gating . The Kinect has been shown to be a valuable tool in various fields of medicine due to its ability to combine a color, infrared, and depth sensor in a single system.…”
Section: Introductionmentioning
confidence: 99%